Boletín Información Documental Vol.1 No. 2 del Centro de Investigaciones en Información Documental (CINFODOC) de los profesores Zapopan Martín Muela Meza y José Antonio Torres Reyes, adscritos a la Facultad de Filosofía y Letras de la Universidad Autónoma de Nuevo León (Mexico) - Muela Meza, Zapopan Martín; Torres Reyes, José Antonio (Dr. Zapopan Martín Muela Meza, 2008)
Second number of the first volume of the Documental Information Bulletin of the Center of Research of Information Recorded in Documents of assistant professors Zapopan Martin Muela Meza and Jose Antonio Torres Reyes who teach librarianship at college level at the School of Philosophy and Letters of the Nuevo Leon Autonomous University, San Nicolas de los Garza, Nuevo Leon, Mexico.